Past, Present, and Future: Superfund, Climate Change, and Environmental Justice - Dougherty, Julia. (Tufts University. Tisch Library., 2024)
Thesis (M.A.)--Tufts University, 2023.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Kathryn Davies.; Committee: Mary Davis.; Keywords: Climate change, Environmental justice, and Environmental health.